Mitochondrial DNA reveals multiple introductions of domestic chicken in East Africa - Mwacharo, Joram M.; Bjornstad, G.; Mobegi, V.A.; Nomura, K.; Hanada, H.; Amano, T.; Hanotte, Olivier H.; Han Jianlin (Elsevier, 2011)
Chicken were possibly domesticated in South and Southeast Asia. They occur ubiquitously in East Africa where they show extensive phenotypic diversity. They appeared in the region relatively late, with the first undisputed evidence of domestic chicken in Sudan, around not, vert, similar 700 BC. We reveal through a detailed analysis of mitochondrial DNA D-loop sequence diversity of 512 domestic village chickens, from four East African countries (Kenya, Ethiopia, Sudan, Uganda), the presence of at least five distinct mitochondrial DNA haplogroups. Phylogeographic analyses and inclusion of reference sequences from Asia allow us to address the origin, ways of introduction and dispersion of each haplogroup. The results indicate a likely Indian subcontinent origin for the commonest haplogroup (D) and a maritime introduction for the next commonest one (A) from Southeast and/or East Asia. Recent introgression of commercial haplotypes into the gene pool of village chickens might explain the rare presence of two haplogroups (B and C) while the origin of the last haplogroup (E) remains unclear being currently observed only outside the African continent in the inland Yunnan Province of China. Our findings not only support ancient historical maritime and terrestrial contacts between Asia and East Africa, but also indicate the presence of large maternal genetic diversity in the region which could potentially support genetic improvement programmes.